Non-invasive Hemoglobin Screening for Detection of Postpartum Anemia - Partha Pratim Das Mahapatra; Nirmal Kumar Mohakud; Chaitali Roy; Harshavardhan Rajagopal; Sandeep Sharma (Women's Health Reports)
Introduction: Postpartum period is a critical period for a woman, where the body of the woman is in healing stage. In this situation, there arises the risk for developing anemia, if proper diet is not maintained. So, it is necessary to routinely determine the hemoglobin levels during this period to avoid chances of developing anemia and assist in early diagnosis. Methodology: A cross-sectional study was carried out at the maternity ward of Kalinga Institute of Medical Sciences Hospital, Bhubaneswar. The study was conducted for a period of 5–6 months by received approval from the concerned institutional committee. The study involved women participants having age above 18 years and who had recently undergone delivery. Written informed consent was taken from all the participants prior to their enrolment for this study. Results: A total of 670 women were involved in this study and more than 50% of the women were found to be affected by anemia. A Pearson’s correlation of 0.87 was observed with sensitivity of 95.69% and specificity of 67.06% between the hematology analyzer and non-invasive EzeCheck device in determining anemia. Conclusion: Women often neglect their health situations and always prioritize their family’s wellbeing and health over their own. This avoidance results in the development of a chronic disease which in the long run becomes difficult to be cured. So, in such situations, it is necessary to inculcate certain routine tests for the women during their healing period (such as postpartum stage) to keep an eye on their health status. Use of non-invasive devices can help in achieving this in a painless and much effective manner with instant reporting of the results.